Handbook of business English - Whalen, Doris H. (New York : Harcourt, Brace, Jovanovich, 1980)
A handbook of English grammar to be used as a text in business English courses or by a business person already on the job. Includes tables, exercises, and a glossary.
Includes index.
Keywords: English language -- Business English; English language -- Business English; English language -- Grammar